Review Article: Amygdalin as Anti-Cancer Agent - Al‐Isawi, Jameelah; abdulhameed, Kawther; Abass, Eiman (Journal of Madenat Alelem University College, 2023)
Amygdalin (d-Mandelonitrile 6-O-β-d-glucosido-β-d-glucoside) and its semi synthetic product is Laetrile ( also called vitamin B17): a natural cyanogenic glycoside occurring in the seeds of some edible plants, such as bitter almonds and peaches. Early in the 19th century, Amygdalin was first isolated in 1830 by two French chemists, Robiquet and Boutron-Charlard, as active components in various fruit pits and raw nuts. However, the systematized study of vitamin B17 started when chemist Bohn (1802) discovered that a hydrocyanic acid is released during distillation of the water from bitter almonds. The various pharmacological effects of Laetrile include anti-atherogenic, activity in renal fibrosis, pulmonary fibrosis, immune regulation, anti-tumor, and anti-inflammatory activities. Despite numerous contributions to the cancer cell lines, the clinical evidence for the anti-cancer activity of Amygdalin is not fully confirmed. Moreover, high dose exposures to Amygdalin can produced cyanide toxicity. In the presented work, pharmacological activity, antitumor activity, and toxicity of Amygdalin have been summarized, focusing primarily on advanced research on Amygdalin and its anti-tumor effects, providing fresh perspectives for the creation of new anti-cancer drugs, the examination of natural antitumor mechanisms, and the search for new targets.